Analysis of Open Source Simulation Applications - Janamanchi, Balaji (Archives of Business Research, 2020)
This study seeks to understanding the growth and popularity of Open Source Software (OSS) development for simulation modeling under Science and Engineering domain on SourceForge online service platform. The objectives include understanding the importance, if any, of the features such as, license type, programming language, Operating System version, review rating in influencing the popularity of a given software application as measured by downloads. For obvious reasons, end-users select and adopt specific applications based on their usage needs and the suitability of a given application in meeting their needs. Nevertheless, some applications may be easily adoptable than the other given the different options available for customization as well as scalability opportunities present in an application. So, other factors remaining common, popularity gained by an application with the increased downloads tends to draw prospective users to a specific application more than the others. This study analyses the availability and accessibility of simulation modeling software on the Source Forge website, undeniably, a very large repository of open source software resources. Limiting the search to “Simulations” within “Science and Engineering” domain /category. The top 250 applications’ data is downloaded and analyzed. Useful insights and metrics are developed and compiled to assist end-users to understand the profile of open source simulation applications available for users for free downloads.